Shelf-life Extension of Pasteurized Mashed Ripe Gros Michel Bananas (Musa sapientum) for Using as an Ingredient in Banana Cake Products - Saisombut, Noppakate; Sukkhown, Pattraporn; Boonpan, Anan (Journal of Food Technology, Siam University, 2024)
This research studied the appropriate conditions for preparing pasteurized mashed ripe Gros Michel bananas (banana puree). The two factors studied were the type and quantity of browning inhibitors. The production of banana cake from pasteurized ripe Gros Michel bananas, the properties of pasteurized ripe golden banana cake and the sensory evaluation of pasteurized ripe golden banana cake were studied. The results of the experiment found that it was possible to increase utilization by extending the shelf life while maintaining the quality of the bananas similar to fresh ripe Gros Michel bananas. The bananas were ground then added with 2% citric acid, packed in vacuum packaging, pasteurized with 15 second heating at 72 oC. It can be stored in the refrigerator at 4 oC for up to 1 month. The result of color showed that banana puree had L* at 72.55, a* at 2.06, and b* at 28.94. The utilization of the mashed banana to make banana cake showed that banana cake formulated with 2% citric acid had a higher adhesiveness and hardness value than that of banana cake (control formula). The results of sensory evaluation with a 9-point hedonic scale method of banana cake product substituted with 25% of mashed- ripe Gros Michel bananas using pasteurization were found that the product sample obtain the preference score of appearance (6.18), color (6.26), overall flavor (5.94), banana flavor (5.92), sweetness (5.98) texture (softness) (5.96), and overall liking (6.00) in the level of “like slightly” and 94% consumer acceptability. Therefore, it is possible to add value of the ripe Gros Michel bananas in the form of pasteurized puree which can extend its shelf-life and process into food products resulting in generating the community income, making more utilization and developing the sustainable economy of country in the future.